Trend-analysis reveals real and placebo rtms effects on addiction craving: a case-control observational study - Casula, Elias Paolo; Chieco, Francesca; Papaioannou, Magdalini Maria; Frizzarin, Fabio; Rocchi, Lorenzo; Camporese, Arianna (Frontiers in Psychiatry, 2025)
Background and aimsRepetitive transcranial magnetic stimulation (rTMS) can be a potential therapeutic tool for the treatment of addiction, thanks to its ability to non-invasively modulate cortical excitability. In the present study, we investigated the short- and the long-term rTMS effects on craving behaviour and psychopathological symptoms in a sample of individuals suffering from gambling and cocaine use disorder.Methods42 individuals (age: 40.7 ± 9.5 years; 40 M) underwent an initial screening testing craving behaviour, by means of visual analogue scales, and psychopathological symptoms, by means of Symptom Checklist-90-R. Participants were subsequently assigned to a real or sham (placebo) rTMS treatment of 2 weeks delivered over the left dorso-lateral prefrontal cortex. To assess the short- and long-term effects of rTMS, participants were evaluated again after 1, 2, 4, 8, 12, 16, 20 and 24 weeks.ResultsAfter an initial similar trend in the craving behaviour of the two groups, our trend analysis showed a long-lasting decrease (until 24 weeks) in the real-rTMS group, following a linear trend (p<0.001); whereas the sham-rTMS group progressively returned to the initial level after about 12 weeks, following a quadratic trend (p<0.001). In addition, we observed moderate-to-strong correlations (0.4<rho<1) showing that placebo effects of rTMS were stronger in individuals showing higher level of psychopathological symptoms for the first 4 weeks.ConclusionsOur results supported a long-term rTMS efficacy for cocaine and gambling craving, for which evidence was still lacking, and the correlation of short-lasting placebo effects and psychopathological symptoms.